1996
DOI: 10.1192/bjp.168.5.556
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Complications and Schizophrenia: A Case Control Study Based on Standardised Obstetric Records

Abstract: The raised incidence of obstetric complications often reported in people with schizophrenia is genuine and probably contributes to the aetiology of the condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
5
4

Year Published

1997
1997
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(112 citation statements)
references
References 19 publications
7
96
5
4
Order By: Relevance
“…Symptoms have included odd sensory experiences and beliefs, sometimes called positive symptoms (Schneider 1959), radically diminished desire, sometimes called negative symptoms (Carpenter et al 1988;Kraeplin 1974), tenuous connections between thoughts (Bleuler 1950;Spitzer 1997), discreet deficits in memory and attention (Green 1996;McGhie and Chapman 1961), autism (Bovet and Parnas 1991), unmodulated anger (Freeman 1969), and social deviance (Szasz 1970). Causal explanations of these symptoms have appealed to factors such as selective abnormalities in neurodevelopment (Andreasen et al 1998), neurological degeneration (Fucetola et al 2000), obstetric complications (Kendell et al 2000), communication deviance (Wahlberg et al 2002), social stigma (Markowitz 1998;Wright et al 2000), and oppressive power relations (Rudge and Morse 2001).…”
mentioning
confidence: 99%
“…Symptoms have included odd sensory experiences and beliefs, sometimes called positive symptoms (Schneider 1959), radically diminished desire, sometimes called negative symptoms (Carpenter et al 1988;Kraeplin 1974), tenuous connections between thoughts (Bleuler 1950;Spitzer 1997), discreet deficits in memory and attention (Green 1996;McGhie and Chapman 1961), autism (Bovet and Parnas 1991), unmodulated anger (Freeman 1969), and social deviance (Szasz 1970). Causal explanations of these symptoms have appealed to factors such as selective abnormalities in neurodevelopment (Andreasen et al 1998), neurological degeneration (Fucetola et al 2000), obstetric complications (Kendell et al 2000), communication deviance (Wahlberg et al 2002), social stigma (Markowitz 1998;Wright et al 2000), and oppressive power relations (Rudge and Morse 2001).…”
mentioning
confidence: 99%
“…Some researchers have shown that pregnancy and birth complications (PBCs) are associated with schizophrenia (McGrath & Murray, 1995), although this has been challenged (Kendell et al, 2000). We have observed that, in Trinidad, with normal rates of schizophrenia, PBCs were actually lower than those reported for the African-Caribbean populations in the UK.…”
Section: Pregnancy and Birth Complicationsmentioning
confidence: 71%
“…Data that were unpublished at the beginning of this study have meanwhile been published or presented at conferences (24)(25)(26)(27). For the two remaining studies (28,29), the raw data on obstetric complications could be scored by the researchers according to the scale of Lewis and Murray. Written informed consent was obtained from all subjects and their relatives who agreed to participate in the studies mentioned above after the procedures had been fully explained.…”
Section: Methodsmentioning
confidence: 99%